(untitled) (In situ, 2024)
Systematic underwater archaeological survey was carried out in the area of the islets of Sv. Fumija and Kraljevac, which are located along the southern coast of the island of Čiovo. A coastal construction of an ancient villa, a chert bed, and individual finds of ancient amphora fragments were found, distributed over a wider area of the examined segment.